THE DEPT LOCATION THE FOUNDATIONS IN SEISMIC AREAS - Rasulov R.H (Web of Journals Publishing, 2025)
In article are stated results of research of authors concerning depth definition location the foundations in seismic areas. The settlement method of depth offered by authors location the foundations is the most simple and effective action for reduction expected procors seismicity construction deformations.